TOTAL QUALITY MANAGEMENT (Journal of Engineering, 2024)
Total quality management is not a new concept. However, it is widely accepted as the fundamental business issue of the 1990s. Companies have started to realize the potential of TQM as a means of ensuring high quality products and services. With this realization has come implementation in rnanufacturing and service companies. Construction companies, like any other business, must provide a top quality finished product to its customer if it intends to stay in business. TQM is one way to work to that errd.Ihe objective of this paper is to review the concept, definition, importance, principles, and elements of total quality management.